Analisis Yuridis terhadap Perlindungan Hukum Konsumen dalam Transaksi Jual Beli Barang Bekas melalui Platform Online di Indonesia - Pramono, Aris Setyanto; Safiulloh; Hadi, Hadi Haerul (UNIVERSITAS SERAMBI MEKKAH, 2024)
The development of information technology has led to an increase in second-hand buying and selling transactions through online platforms in Indonesia. Although offering convenience and accessibility, these transactions also carry various risks, especially regarding legal protection for consumers. This study aims to analyze the juridical aspects of consumer legal protection in online buying and selling of used goods, with a focus on the applicable regulations and the challenges faced in their implementation. This study uses a normative juridical method with a legislative approach and case studies. The results show that despite the existence of various regulations designed to protect consumers, such as Law No. 8/1999 on Consumer Protection and Government Regulation No. 80/2019 on Electronic Commerce, the implementation of legal protection in the context of buying and selling used goods online still faces significant obstacles. The main problems found are the lack of transparency of information, the lack of supervision of sellers, and difficulties in enforcing consumer rights when disputes occur. This study concludes that more specific regulatory adjustments and increased supervision are needed to ensure more effective protection for consumers in buying and selling second-hand goods through online platforms. In addition, educating consumers about their rights and enforcing their rights is also needed.